Caries experience in 7‐, 12‐, and 15‐year‐old schoolchildren in the canton of Basel‐Landschaft, Switzerland, from 1992 to 2011. Issue 3 (28th December 2015) - Waltimo, Tuomas; Menghini, Giorgio; Weber, Catherine; Kulik, Eva M.; Schild, Samuel; Meyer, Jürg
Abstract: Objectives: To investigate the changes in caries experience and prevalence among schoolchildren of the canton of Basel‐Landschaft, Switzerland, over the course of 20 years. Methods: A random sample of either schoolchildren aged 7, 12, and 15 years (in 1992) or aged 12 and 15 years (in 1997) or their respective school classes (2001, 2006 and 2011) was selected so that approximately 10% of schoolchildren could be examined. The children's dmft and DMFT scores were determined according to the WHO methodology and analyzed using cluster‐adjusted ordinary multiple linear regression modeling. Results: For all age groups, the respective dmft/DMFT values decreased steadily from 1992 to 2006 but increased again in 2011. However, the observed differences were not statistically significant over the examination years from 2001 to 2011. Schoolchildren with a migrant background had approximately two‐ to threefold higher dmft/DMFT values. Conclusions: In the years from 1992 to 2001, a steady decline in caries was observed in all age groups of schoolchildren examined in the canton of Basel‐Landschaft. However, in the subsequent 10 years, this decline has leveled off. The mean dmft/DMFT values are comparable to those in other parts of Switzerland. Migrants are a caries‐risk group; the mean dmft/DMFT values were higher in schoolchildren with a migrant background than in the comparable Swiss children.